Antineutrophilic Cytoplasmic Antibody–Positive Vasculitis Associated With Thromboangiitis Obliterans in a Middle-Aged Man - Naushad Abid; Hamzah Naushad Siddiqui (Annals of Internal Medicine: Clinical Cases)
Antineutrophilic cytoplasmic antibody (ANCA)-associated vasculitides are autoimmune diseases with multisystem manifestations. We report the case of a 55-year-old Asian man with a history of cigarette smoking who presented with ischemic lesions of the extremities, a positive ANCA, and crescentic glomerulonephritis. We entertained the diagnosis of ANCA-positive vasculitis associated with thromboangiitis obliterans, a nonatherosclerotic inflammatory vascular disorder. The patient responded well to a combination of immunosuppressive medications and smoking cessation. Cigarette smoking could be a common pathogenic factor in both conditions. To our knowledge, this is the first case of its kind describing an association between ANCA-associated vasculitis and possible thromboangiitis obliterans.